PTTG1 is involved in TNF‐α‐related hepatocellular carcinoma via the induction of c‐myc - Lin, Xianyi (Cancer Med, 2019)
Hepatocellular carcinoma (HCC) is a malignant disease caused by a variety of factors. However, the genomic and molecular aberrations in HCC are largely unknown. Herein, pituitary tumor transforming gene 1 (PTTG1) was discovered as a potential inflammation‐related oncogene in HCC, and its functions and molecular mechanisms were investigated. mRNA expression microarray, real‐time polymerase chain reaction (PCR), immunohistochemistry, and western blotting analyses revealed that PTTG1 is upregulated in HCC. Further in vitro and in vivo studies indicated that the proinflammatory cytokine tumor necrosis factor‐α (TNF‐α) induces PTTG1 expression, and PTTG1 was found to upregulate c‐myc, a well‐known oncogene. Downregulation of PTTG1 reduced c‐myc and proliferating cell nuclear antigen (PCNA) expression and inhibited cell proliferation. Interestingly, inhibition of c‐myc by 10058‐F4 did not affect PTTG1, which suggests that PTTG1 regulates c‐myc expression. Furthermore, PTTG1 expression levels are inversely correlated with HCC patient survival, indicating an independent prognostic biomarker for patients with HCC. Our data demonstrate that PTTG1 is involved in TNF‐α‐related HCC via c‐myc induction and that PTTG1 may be a potential therapeutic target for HCC.